Manipulation of extrinsic and intrinsic language styles in the scripts Menunggu Lampu Hijau and My Honey - Othman, Shamsudin; Abdullah, Nur Afifah Vanitha (Human Resource Management Academic Research Society, 2023)
In the history of modern Malay drama, Hatta Azad Khan is the first playwright to have written, directed and staged ‘adult content’ plays in Malaysia. Menunggu Lampu Hijau and My Honey was published by Dewan Bahasa and Pustaka Malaysia (DBP) in 2015, in a book entitled OTG. Both plays were organised and staged for public in several institutions in Malaysia. This article aims to answer, how Hatta manipulated language to convey adult content in his plays, which DBP has published without any issue? Thus, a research was conducted to study Hatta’s credential and language as a playwright in both plays. A qualitative research was designed with library research and interview as research tools. Interviews were conducted with actors of both plays, and officers at the publication department of DBP. Content analysis was carried out on both the scripts and performance texts on stage. The findings documented in this article are that, there are extrinsic and intrinsic factors that enable both plays by Hatta to be staged and published. The extrinsic factor is Hatta has employed his 50 years of playwriting knowledge and experience in Malay drama to produce his plays. Meanwhile the intrinsic factor is that, the playwright has manipulated and aligned his language to suit the comedy genre that underlies the scripts. Besides metaphor, he has applied syncope and foreign language to triger humor and convey adult content in a very polite manner. These factors had enabled Hatta to publish and stage both his plays in Malaysia.